Picky eating and stunting in children aged 2 to 5 years in central Lampung, Indonesia - Yesi Nurmalasari; Deviani Utami; Brian Perkasa (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2020)
Background: The difficulty of feeding (picky eater) is the behavior of the child does not want to or refuses to eat, or have difficulty consuming food or drink with the type and quantity of suitable age physiologically (natural and unnatural), ranging from open his mouth without coercion, chew, swallow, until absorbed in digestion are good without coercion and without granting specific medications, vitamins and Picky eater able to be symptoms of child health detriment if the reply was not directly addressed. A picky eater can make a child's nutritional intake shortage that certainly further cause severe Stunting and is easily affected by the disease.Purpose: Knowing correlation between toddler's picky eater and stunting on toddler in Central Lampung- Indonesia.Methods: This study used a quantitative approach to the design of case- control. Sampling techniques using the formula slovin. Data analysis using the chi- square test.Results: The statistical tests for non-parametric bivariate obtained the value of p = 0.000 picky eater relationship with stunting which means there is a significant correlation.Conclusion: There is a relationship between picky eater with a stunting incident in Central Lampung Indonesia. Suggestion for government authority to be pay attention especially in compliance of the nutritional needs to toddler and health education to the parent about an essential nutrition for the toddler